PENGGUNAAN KETUM DALAM RAWATAN PENYAKIT MENURUT PERSPEKTIF HUKUM ISLAM SEMASA: ANALISIS TERHADAP PANDANGAN PAKAR: The Use of Kratom in Medicine From Islamic Perspective: Analysis on Expert Views - Man, Sa’adan; Ali, Abdul Karim; Abdul Rahman, Noor Naemah; Pauzi, Norhidayah; Isa, Noor Munirah; Ali Besar, Mohammad Nasharudin (Jurnal Syariah, 2024)
Ketum, or its scientific name, Mitragyna speciosa Korth. (M. speciosa Korth.), is a type of natural herb plant that grows in the north of the peninsula of the country, Malaysia, especially in Perlis and Kedah. Other countries, particularly in Southeast Asia, such as Indonesia and Thailand, are also home to this plant. Basically, ketum has been used for a long time as one of the traditional treatment sources by the local community. It is believed to be able to provide energy nutrients, help in the treatment of diabetes, diarrhea, worms, gout, high blood pressure, increase appetite and inner energy. This study was conducted to look at the benefits and harms of ketum, identify its use from the perspective of current Islamic law and evaluate the acceptance of ketum according to the views of experts representing various fields of medicine, science, pharmacy, law and syariah. This study uses a literature and field data collection methodology. Furthermore, the data that have been collected are analyzed based on inductive, deductive and comparative patterns. This study found that ketum has a high medicinal value, supported by scientific evidence. From an Islamic perspective, the origin of the use of ketum is permissible, but several current variable factors seem to have a significant impact on its prohibition. Therefore, the acceptance of the use of ketum for the treatment of diseases legally needs to go through several important phases, such as scientific evidence, legislation and control mechanisms.